SSCP video mentor - Harris, Shon (Pearson, 2010)
"SSCP Video Mentor teaches the more challenging topics on the SSCP exam. This visual learning experience from a leading topical expert helps make otherwise difficult concepts understandable through video tools, conversational audio, and the ability to watch an expert put the knowledge into real application. The dozens of hours of classroom instruction is enhanced with flash animations, screencasts, scenario-based case studies and labs designed to work together to provide both foundational learning on the topic as well as exam preparation skills. The videos tackle each SSCP topical area with in depth learning that teaches you what you need to understand, not only to pass the exam, but to apply it in the workplace. The classroom instruction is enhanced with the multimedia learning tools to help the expert instructor teach you these topics so that you grasp them for real world application and exam success"--Resource description page.